Metabolic strategies of melanoma cells: Mechanisms, interactions with the tumor microenvironment, and therapeutic implications. (2nd November 2017) - Fischer, Grant M.; Vashisht Gopal, Y. N.; McQuade, Jennifer L.; Peng, Weiyi; DeBerardinis, Ralph J.; Davies, Michael A.
Summary: Melanomas are metabolically heterogeneous, and they are able to adapt in order to utilize a variety of fuels that facilitate tumor progression and metastasis. The significance of metabolism in melanoma is supported by growing evidence of impact on the efficacy of contemporary therapies for this disease. There are also data to support that the metabolic phenotypes of melanoma cells depend upon contributions from both intrinsic oncogenic pathways and extrinsic factors in the tumor microenvironment. This review summarizes current understanding of the metabolic processes that promote cutaneous melanoma tumorigenesis and progression, the regulation of cancer cell metabolism by the tumor microenvironment, and the impact of metabolic pathways on targeted and immune therapies.